Exosomes derived from mature chondrocytes facilitate subcutaneous stable ectopic chondrogenesis of cartilage progenitor cells - Chen, Yahong (Stem Cell Res Ther, 2018)
BACKGROUND: Developing cartilage constructed with the appropriate matrix composition and persistent chondrogenesis remains an enduring challenge in cartilage defects. Cartilage progenitor cell (CPC)-based tissue engineering has attracted recent attention because of its strong chondrogenic differentiation capacity. However, due to the lack of a suitable chondrogenic niche, the clinical application of CPC-regenerated cartilage in the subcutaneous environment remains a challenge. In this study, exosomes derived from chondrocytes (CC-Exos) were used to provide the CPC constructs with a cartilage signal in subcutaneous environments for efficient ectopic cartilage regeneration. METHODS: Rabbit CPC-alginate constructs were prepared and implanted subcutaneously in nude mice. CC-Exos were injected into the constructs at the same dose (30 μg exosomes per 100 μL injection) after surgery and thereafter weekly for a period of 12 weeks. Exosomes derived from bone mesenchymal stem cells (BMSC-Exos) were used as the positive control. The mice in the negative control were administered with the same volume of PBS. At 4 and 12 weeks after implantation, the potential of CC-Exos and BMSC-Exos to promote chondrogenesis and stability of cartilage tissue in a subcutaneous environment were analyzed by histology, immunostaining, and protein analysis. The influences of BMSC-Exos and CC-Exos on chondrogenesis and angiogenic characteristics in vitro were assessed via coculturing with CPCs and human umbilical vein endothelial cells. RESULTS: The CC-Exos injection increased collagen deposition and minimized vascular ingrowth in engineered constructs, which efficiently and reproducibly developed into cartilage. The generated cartilage was phenotypically stable with minimal hypertrophy and vessel ingrowth up to 12 weeks, while the cartilage formed with BMSC-Exos was characterized by hypertrophic differentiation accompanied by vascular ingrowth. In vitro experiments indicated that CC-Exos stimulated CPCs proliferation and increased expression of chondrogenesis markers while inhibiting angiogenesis. CONCLUSIONS: These findings suggest that the novel CC-Exos provides the preferable niche in directing stable ectopic chondrogenesis of CPCs. The use of CC-Exos may represent an off-the-shelf and cell-free therapeutic approach for promoting cartilage regeneration in the subcutaneous environment.